PEMANFAATAN DAUR ULANG SAMPAH SEBAGAI MEDIA PEMBELAJARAN BIOLOGI DI SEKOLAH - Eko Sri Wahyuni; Titin Titin; Mas Akbar Faturrahman (Bioilmi: Jurnal Pendidikan, 2022)
The waste and garbage have been widely used to produce new goods with a high enough value and price. Besides being produced for marketing and making money, waste can also be used as learning media. Learning media in the teaching and learning process has benefits, namely clarifying messages so that they are not too verbalized, overcoming space, time, energy and senses, and creating a passion for learning because there is a direct interaction between students and learning resources so that teaching and learning situations are more effective. This study aims to determine the types of learning media that can be made from waste or garbage and the feasibility of the resulting learning media. This research was conducted at FKIP, University of Tanjungpura from February to March 2022. This research is a descriptive quantitative with research stages include making learning media and validating the learning media that have been made. Validity was carried out using CVR and CVI calculations. The results showed that the seventh learning media each had a CVI value of 0,99. The CVI value shows the suitability of teaching aids with the material, the relationship between teaching aids and the level of learning needs, and teaching aids can explain material systematically and clearly. Functional learning media from used goods is valid and can be used in Biology learning activities in schools.